Electrospun nanofibers of Tin phosphide (SnP0.94) nanoparticles encapsulated in a carbon matrix: a tunable conversion-cum-alloying lithium storage anode - Yadav, Poonam; Malik, Wahid; Dwivedi, Pravin Kumari; Jones, Lathe A.; Shelke, Manjusha V. (Energy & Fuels, 2020)
Anodes with improved Li storage capability are required for next-generation lithium batteries. In this work we report a convenient synthesis strategy, based on electrospinning followed by reduction and phosphorization, to prepare a tin phosphide (SnP0.94) phase in a carbon nanofiber matrix. The layered structure offered by the SnP0.94 phase, along with its small size (5-20 nm) encapsulated in the conducting carbon matrix, leads to promising electrochemical Li storage characteristics. This composite has a capacity of 750 mAh g(-1) at 100 mA g(-1) with good cycling and rate stability. Electrochemical studies revealed a faster diffusion coefficient (1.86 x 10(-11) cm(2) s(-1)) for Li in the composite compared to the bare SnP0.94 (8.57 x 10(-14) cm(2) s(-1)), confirming the promise of this class of materials for cation storage in battery anodes.